1980
DOI: 10.1111/j.1442-9993.1980.tb01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Throughfall and stemflow on silverleaf ironbark (Eucalyptus melanophloia) trees

Abstract: The redistribution of rainfall on silverleaf ironbark (Eucalyptus melanophloia) trees in a semiarid environment at Narayen Research Station has been studied using detailed measurements on four trees.Interception accounts for about 11% of the annual rainfall with only 0.6% as stemflow; canopy storage capacity is estimated to be 2 mm and an estimate of the rain required to initiate stemflow is 7 mm.With the exception of nitrogen, the amounts of major elements returned to the soil surface beneath the tree canopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…1, and 16.8% of the gross rainfall for the entire study period. Park (2000) indicated that total basal area was the primary factor controlling the difference in the ratio of throughfall and stemflow between two stands in the region, considering the various species present (Brown and Barker, 1970;Prebble and Strick, 1980;Valente et al, 1997;Crockford and Richardson, 1990). The relationship between total basal area and each ratio was also valid at this site, implying that the ratio of interception loss at a stand may be mainly determined by basal area, regardless of size distributions or stand density.…”
Section: Throughfall and Stemflow In A Mixed-species And -Size Forestmentioning
confidence: 90%
“…1, and 16.8% of the gross rainfall for the entire study period. Park (2000) indicated that total basal area was the primary factor controlling the difference in the ratio of throughfall and stemflow between two stands in the region, considering the various species present (Brown and Barker, 1970;Prebble and Strick, 1980;Valente et al, 1997;Crockford and Richardson, 1990). The relationship between total basal area and each ratio was also valid at this site, implying that the ratio of interception loss at a stand may be mainly determined by basal area, regardless of size distributions or stand density.…”
Section: Throughfall and Stemflow In A Mixed-species And -Size Forestmentioning
confidence: 90%
“…Consequently, the effects of one factor can be confounded with the effects of the other. In any case, as just suggested, there may be a correlation of intensity and stemflow delivery only in certain intensity classes, and this might be concealed when event means are examined.A third group of studies has reported that stemflow yield rises under increasingly intense rainfall (Prebble and Stirk, ; Van Elewijck, ; Crockford and Richardson, ; Aboal et al ., ; Owens et al ., ). For instance, Aboal et al .…”
Section: The Influence Of Rainfall Intensity On Stemflow Yieldmentioning
confidence: 97%
“…(c) A third group of studies has reported that stemflow yield rises under increasingly intense rainfall (Prebble and Stirk, 1980;Van Elewijck, 1989;Crockford and Richardson, 1990;Aboal et al, 1999;Owens et al, 2006). For instance, Aboal et al (1999) related funnelling ratio FR (dimensionless) to mean hourly rainfall intensity (I, in mm/h) in Erica arborea and other plants as…”
Section: The Influence Of Rainfall Intensity On Stemflow Yieldmentioning
confidence: 99%
“…Th is process can be responsible for leaching nutrients from canopy leaves and transporting them to the forest fl oor (Parker 1983). In some particular cases, throughfall may exceed incident precipitation in quantity, e.g., under fog precipitation (Zinke 1962;Banaszak 1975;Prebble & Stirk 1980). Th roughfall includes incident precipitation which penetrates canopy gaps unless the individual canopy gaps are large and frequent (Parker 1983).…”
Section: Introductionmentioning
confidence: 99%